Pengaruh Self Assessment System, Kesadaran Wajib Pajak Dan Account Representative Terhadap Kepatuhan WPOP Yang Melakukan Kegiatan Usaha Dan Pekerjaan Bebas Dengan Preferensi Risiko Sebagai Variabel Moderating - Fitriasuri Fitriasuri; Kristina Ardila (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine the effect of the self-assessment system, taxpayer awareness, and account representative on the compliance of individual taxpayers who carry out business activities and independent work. individual taxpayer compliance, the effect of risk preference which acts as a moderating variable of the relationship between taxpayer awareness of individual taxpayer compliance, and the effect of risk preference which acts as a moderating variable of the relationship between account representatives and individual taxpayer compliance. This research was conducted by non-probability sampling method with a sample of 100 respondents from individual taxpayers. The data used are primary data through a questionnaire containing the respondents' answers. The data analysis used in this research is Moderated Regression Analysis. The results of this study show that the self-assessment system has a negative effect, while taxpayer awareness and account representation has a positive effect on individual taxpayer compliance. In addition, the risk preference moderating variable is not able to moderate the effect of the self-assessment system on individual taxpayer compliance, while the risk preference moderating variable can moderate the effect of taxpayer awareness and account representative on individual taxpayer compliance.